The Coupling between Entrepreneurship and Public Policy: Tight in Developed Countries but Loose in Developing Countries - Schøtt, Thomas (Estudios de Economía, 2016)
In this paper we compare the coupling between entrepreneurship policy and entrepreneurship activity in developed and developing countries. Using new institutional arguments, we argue that developing countries are prone to implement policies that (1) are based on experiences in developed countries which have not proven to transfer fittingly to developing economies, (2) are only partly implemented and are not internally consistent as a result of a lack of resources to do so, and (3) are more beneficial on paper than on actual activity. Following this perspective, the coupling between entrepreneurship policy and entrepreneurship activity is hypothesized to be lower for developing countries than for developed countries. Using GEM data correlating the TEA index of early-phase entrepreneurship with indicators of policies obtained from key expert informants supports this proposition.